2016
DOI: 10.1093/aob/mcw220
|View full text |Cite
|
Sign up to set email alerts
|

Comparative seed germination and seedling development of the ghost orchid,Dendrophylax lindenii(Orchidaceae), and molecular identification of its mycorrhizal fungus from South Florida

Abstract: Background and Aims The endangered leafless ghost orchid, Dendrophylax lindenii, one of the most renowned orchids in the world, is difficult to grow under artificial conditions. Published information on asymbiotic and symbiotic (co-culture with a mycobiont) seed germination, seedling anatomy and developmental morphology of this leafless orchid is completely lacking. This information is critical for the development of efficient procedures for ghost orchid production for successful reintroduction.Methods Ghost o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 54 publications
0
43
0
2
Order By: Relevance
“…Plants of the remaining treatments continued in the vegetative stage. Hoang et al (2017) reported a similar flowering phenomenon in some plants from ghost orchid (Dendrophylax lindenii), after two years of in vitro germination on symbiotic conditions. Indeed, we are convinced that this reproductive precocity is a consequence of the benefits of the orchid-mycorrhizal symbiosis, allowing an increase in plant growth and development.…”
Section: Culture Mediamentioning
confidence: 70%
“…Plants of the remaining treatments continued in the vegetative stage. Hoang et al (2017) reported a similar flowering phenomenon in some plants from ghost orchid (Dendrophylax lindenii), after two years of in vitro germination on symbiotic conditions. Indeed, we are convinced that this reproductive precocity is a consequence of the benefits of the orchid-mycorrhizal symbiosis, allowing an increase in plant growth and development.…”
Section: Culture Mediamentioning
confidence: 70%
“…For histological preparation, seeds and protocorms (0-8 weeks after planting) were treated using paraffin method following the method of Hoang, Kane, Radcliffe, Zettler, & Richardson (2017). The anatomy slides were observed by a light microscope.…”
Section: Histological Preparation Of Protocorm Samplesmentioning
confidence: 99%
“…The mean D. lindenii nectar spur length measured on artificially propagated plants (n = 102) was 136.5 mm (H. Ray, personal communication). These artificially propagated plants were grown from D. lindenii seeds that were collected on the Florida Panther National Wildlife Refuge (Hoang et al 2016). Nectar spur lengths measured on 5 natural Florida Panther National Wildlife Refuge D. lindenii flowers ranged from 90 to 120 mm, and averaged 100 mm (M. LaRusso & J. Lu, personal communication).…”
Section: Resultsmentioning
confidence: 99%
“…For orchid conservation to be successful, Swarts and Dixon (2009) proposed 3 actions that must be met: (1) management of natural reserves with emphasis on the specialized needs of orchids (e.g., pollinators, mycorrhizal fungi); (2) establishment of ex situ seed and mycorrhiza banks for orchids under immediate threat; and (3) development of orchid restoration techniques. For D. lindenii, all 3 of these actions have been achieved largely due to coordinated research efforts in southern Florida and Cuba during the past decade (see Hoang et al 2016;Mujica et al 2018;Zettler et al 2019;Coopman & Kane 2019). Collectively, all of these efforts have aligned in favor of D. lindenii with 1 important exception -virtually no information existed on the pollination biology of the ghost orchid until now.…”
Section: Implications For Conservation In Florida and Cubamentioning
confidence: 99%
See 1 more Smart Citation